PENGARUH MODAL USAHA DAN TINGKAT PENGALAMAN BERWIRAUSAHA TERHADAP KINERJA UMKM PERKEBUNAN BUAH NAGA DI DESA LESTARI DADI KECAMATAN PEGAJAHAN KABUPATEN SERDANG BEDAGAI - vinka lorenza; Nur'ain Harahap (JURNAL MANAJEMEN DAN BISNIS, 2022)
The implementation of this study was to determine whether there was an influence between venture capital and the level of entrepreneurial experience on the performance of UMKM in dragon fruit plantations in Lestari village. This study uses descriptive analysis and quantitative analysis, with a sample of 35 small and medium enterprises UMKM in dragon fruit plantations. This research was carried out by giving questionnaires to the perpetrators of UMKM in dragon fruit plantations. This study shows the results that the business capital factor and the level of entrepreneurial experience have an influence on the performance of UMKM in dragon fruit plantations in Lestari village, which is shown from the results of multiple regression Y= 4.268+0.372X1+0.385X2+e. The results of the partial test (t test) of venture capital on the performance of UMKM in dragon fruit plantations, the value of tcount = 2.371>1.69 and the results of the partial test (t test) of entrepreneurial experience obtained the value of tcount = 2.136>1.69, it is stated that partial factors of venture capital and entrepreneurial experience have a positive and significant effect on the performance of UMKM in dragon fruit plantations in Lestari village, in addition to the F test the results show that Fcount>Ftable (23.919>3.294) with a probability level (0.01<0.05). The value of the coefficient of determination (R2) of 0.599 means that business capital and entrepreneurial experience can improve the performance of UMKM in dragon fruit plantations in Lestari village with an R2 value of 59.9% and the remaining 40.1% is explained by other variables outside the study.